Images of the Recent Past From the Cinematographic and Audiovisual Production of the Province of Tucumán, Northwest Region of Argentina - Lusnich, Ana Laura (2025)
This article aims to analyze a significant set of films and audiovisual pieces made in the province of Tucumán, belonging to the Northwest region of Argentina, which covered the last military governments and had a special focus on Operation Independence, that, occurred in Tucumán in 1975, constituted the prelude to the coup d’état of 1976. One of the objectives is to identify, from this corpus, the modes of representation and the expressive forms that dominated in this region during the long period of time about the problems of the recent past. The second objective is to analyze the importance of this corpus in the local and national historical and political panorama, investigating the revision of regional history and the construction of provincial and regional memories about the historical periods covered.